Impact of prematurity on early child cognitive development - Paolini, Cynthia Inés (2016)
Objectives: The aim of this research is to contribute to the understanding of the consequences of prematurity on cognitive development, in early childhood. Study the prevalence of cognitive developmental difficulties in preterm infants. Identify risk factors. And compare cognitive development of preterm children with those born at term. Methods: Cross-sectional descriptive study design. Argentine scale of sensory motor intelligence (EAIS) was administered to assess cognitive development. Frequency of cognitive delay, neonatal and sociodemographic risk factors were studied, using multivariate regression models, adjusting for confounders. The risk of cognitive difficulties by degree of prematurity, compared with term infants was calculated. Results: A total of 232 preterm and 214 term infants, were evaluated. The frequency of cognitive impairments in premature is significantly higher than in term infants. The risk of delay in cognitive development increases with decreasing Gestational age [GA]. Late preterm infants also are at higher risk of cognitive delay than those born at term. Cognitive difficulties tend to increase as the child grows. The motor area was the most committed psychomotor area. The evaluated correlation between both cognitive and psychomotor areas was moderate. Gestational age, birth weight [BW], intrauterine growth retardation [IUGR] and neonatal complications are risk factors for early cognitive development. The paternal education is associated with cognitive development.